(untitled) (Journal of Medicine, 2009)
Background: An event of stroke can be ignited by a number of risk factors, some of which are nonmodifiable and some are modifiable. Hypertension, diabetes mellitus, different heart diseases, hyperlipidemia and smoking belong to the latter group and their prevalence shows immense diversity worldwide. In this study we tried to identify the most prevalent risk factor for stroke. Categorization of various types of stroke and history of noncompliance in medication has also been evaluated. Methods: This direct observational study was carried out on 400 patients of stroke admitted in different medicine units of Dhaka Medical College Hospital from July to December, 2007. Only patients having clinical diagnosis of stroke, confirmed by CT scan or MRI, were recruited. Patients were grouped into ischemic or hemorrhagic stroke or sub arachnoid hemorrhage. Results: The male, female ratio was found 1.2:1. In the study cerebral infraction, intra cerebral hemorrhages (ICH) and sub arachnoid hemorrhage (SAH) were found in 56.25%, 38.25% and 5.5% patients respectively. In case of Ischemic stroke and ICH males were predominantly affected but in case of SAH females were predominant. Among patients, hypertension was found in 58.62% followed by smoking (53.79%), lipid disorder (48.01%), heart diseases (25.75%), diabetes mellitus (20.01%), and previous history of stroke (10.61%). 40% patients were on irregular use of antihypertensive drug and it was 17.5% in case of anti diabetic drugs. Major groups (42.44%) of patients have two modifiable risk factors. Conclusion: Stroke is better to prevent than to cure. Identification of risk factors is the only way to achieve this goal. Implementation of screening programme in community to identify risk factors and educate people about primary prevention should be initiated in this regard. This way, we can reduce morbidity and mortality among stroke patients and alleviate the burden of stroke. Â doi:10.3329/jom.v10i3.2011 Â J Medicine 2009; 10 (Supplement 1): 18-21